Morphometric and genetic evidence for cryptic diversity in Gyrodactylus (Monogenea) infecting non-native European populations of Ameiurus nebulosus and A. melas. Issue 14 (30th December 2020) - Ondračková, Markéta; Seifertová, Mária; Bryjová, Anna; Leis, Eric; Jurajda, Pavel
Abstract: Gyrodactylid parasites were observed on non-native populations of North-American freshwater catfishes, Ameiurus nebulosus and Ameiurus melas (Siluriformes: Ictaluridae), at several sites in the Elbe River basin, Czech Republic, Europe. Using a combination of morphological and genetic analyses, the parasites infecting A. nebulosus were determined to be Gyrodactylus nebulosus, a North American parasite co-introduced to Europe along with its Ameiurus fish hosts. Subtle morphometrical differences, as well as seasonal variations, were observed among parasites collected from A. nebulosus and A. melas . The host-related variation was further supported through genetic analysis of the partial 18S rDNA, ITS1-5.8S-ITS2 and COI, showing 0.2, 3.0 and 4.8% divergence, respectively. Consistent genetic differences indicated there were two distinct genotypes. Subtle morphological differences associated with the shape of sickle toe, anchor root and ventral bar membrane, according to host species, also supported the description of a new cryptic species, Gyrodactylus melas n. sp., infecting A. melas . Multivariate morphometrical analysis of haptoral hard parts showed significant differences between the anchor lengths of G. nebulosus and G. melas n. sp. However, the measurements of the haptoral hard structures partially overlapped between species, limiting the usage of these parameters for species delineation.